Proses Stripping, Stuffing dengan Distribusi Sparepart Excavator pada Gudang Pusat Logistik Berikat - Salsabila Aprilianda; Yuda Yulianto; Agus Setiawan (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of this study was to investigate the correlation of stripping process and stuffing process of Excavator distribution at PLB ware house Kawasan Berikat Nusantara company. The problem in this research is the limitation of operational equipment, lack of maintenance service of operational equipment, and lac of number of employees. Quantitatif method with multiple linera regression technique was used in this research. There were 28 employees as sample. The result shows that the stripping process and stuffing process were significant positive relation with spareparts distribution Excavator at Kawasan Berikat Nusantara company.